Implication of Child Marriage on Character Building: Case Study in Gajah Mungkur Reservoir Area Wonogiri 2011-2017 - Lubis, Erni Sari Dwi Devi; Jamuin, Ma’arif (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
The subject of this study is the phenomenon of child marriage or early marriage in the area of Gajah Mungkur Reservoir, Wonogiri, particularly related with its implication on the character building. In this area, child marriage has been practiced and traditionally carried out by the local community of 12-20 years in age. Despite the tendency of declining marriage number since 2000, the phenomenon is still rampant. Nevertheless, it has adverse impacts on the effort to build the national character for the future. It implies on the achievements of the Nawa Cita declared by Jokowi and Jusuf Kalla, especially priorities 3, 5, 8, and 9, within the framework of Overhauling the Character of the Nation.This study investigates the problems linked to child marriage, which cover the main factors of poverty, low educational background, communal traditional values, negative social value shift, low awareness of self-development, and low level of scientific literacy. The government, actually, has devised some measures to address this issue, yet they fail to solve the fundamental issue. This phenomenon influences the character building of society towards the ideal characters aspired by the Indonesian nation at least as stated in the Nawa Cita.The data of this study were collected through observation, documentation and in-depth interview. Furthermore, they were analyzed using an eclective technique by simultaneously employed deductive and inductive analysis framework in an attempt to explicate the relationship and implication among various aspects within the issue.